What Determines the Current Account? : A Cross-Sectional and Panel Approach - Faruqee, Hamid; Debelle, Guy. (Washington, D.C. : International Monetary Fund, 1996)
This paper uses cross-section and panel data to examine the determinants of the current account. The empirics find a significant impact of the stage of development and demographic factors in the cross section. Estimating partial-adjustment and error-correction models using panel data, the paper finds a short- and long-run impact of fiscal policy on the current account in the time series. The real exchange rate, the business cycle and the terms of trade are also shown to have short-run effects on the current account, while the stage of development and demographics have longer-run effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet